Assessment of genetic diversity in Tamarind (Tamarindus indica L. ) using random amplified polymorphic DNA markers (SAARC Journal of Agriculture, 2015)
Determination of genetic variation is important to the plant breeders for development of high yielding variety. The aim of the current study was to investigate the genetic diversity of nine tamarind cultivars, out of nine four flowering cultivars using random amplified polymorphic DNA (RAPD) markers. Ten Random amplified polymorphic DNA (RAPD) primers were used to assess the genetic diversity in four flowering cultivars and five non-flowering of tamarind trees. The average genetic similarity level among the four flowering cultivars and five non-flowering accessions grouped into six clusters groups at 0.76%. RAPD profiles of all the tamarind were compared and a total of 58 scorable bands were produced with seven primers ranging from one for OPG-13 to twelve for OPA-R15. Genotypes which were morphological closely related were found to be unrelated at the molecular level. A sizeable amount of intrapopulation diversity recorded in the present study which can be utilized in hybridization programmes to efficiently introgress the desirable trait of interest.SAARC J. Agri., 13(1): 27-36 (2015)